Thermal Performance Curves Reveal Variation in the Seasonal Niche of a Short-Lived Annual. (25th July 2017) - Hereford, Joe
Synopsis: An organism's environment can vary over spatial and temporal scales. Seasonal variation is an important but overlooked source of environmental variation that often shapes the ranges of organisms. The seasonal niche is a description of the spatiotemporal range of an organism resulting from spatial variation in seasonal conditions. In this study, I describe the seasonal niche of a short-lived annual plant, and variation within the species in seasonal niche breadth. I construct a seasonal species distribution model (SDM) for the species, and using thermal performance curves (TPCs), construct mechanistic SDMs (MSDMs) for individual genotypes. I quantify the correlation between the suitability scores generated in the SDM and the predicted dry weight generated by the MSDMs for each genotype, to estimate variation in seasonal niche breadth among genotypes. Thus, the parameters of TPCs reflect generalist/specialist strategies. I detected significant relationships between thermal performance breadth and maximum predicted fitness and significant correlations between optimal growth temperature and thermal performance breadth. There were large positive correlations between predictions of the SDM and MSDMs based on growth within individual genotypes. The variation in these correlations suggests variation in the degree of specialization. Genotypes with the broadest TPCs had the largest correlations between their MSDMs and the SDM, suggesting that they were generalists. The results show that correlative and MSDMs make similar predictions over the seasonal range, and that ecological specialization can vary dramatically within species.